Scrutinizing the feasibility of macroscopic quantum coherence in the brain: a field-theoretical model of cortical dynamics - Keppler, Joachim (Frontiers in Physics, 2023)
The neural activity patterns associated with advanced cognitive processes are characterized by a high degree of collective organization, which raises the question of whether macroscopic quantum phenomena play a significant role in cortical dynamics. In order to pursue this question and scrutinize the feasibility of macroscopic quantum coherence in the brain, a model is developed regarding the functioning of microcolumns, which are the basic functional units of the cortex. This model assumes that the operating principle of a microcolumn relies on the interaction of a pool of neurotransmitter (glutamate) molecules with the vacuum fluctuations of the electromagnetic field, termed zero-point field (ZPF). Quantitative calculations reveal that the coupling strength of the glutamate pool to the resonant ZPF modes lies in the critical regime in which the criterion for the initiation of a phase transition is fulfilled, driving the ensemble of initially independent molecules toward a coherent state and resulting in the formation of a coherence domain that extends across the full width of a microcolumn. The formation of a coherence domain turns out to be an energetically favored state shielded by a considerable energy gap that protects the collective state against thermal perturbations and entails decoherence being greatly slowed down. These findings suggest that under the special conditions encountered in cortical microcolumns the emergence of macroscopic quantum phenomena is feasible. This conclusion is further corroborated by the insight that the presence of a coherence domain gives rise to downstream effects which may be crucial for the cortical communication and the formation of large-scale activity patterns. Taken together, the presented model sheds new light on the fundamental mechanism underlying cortical dynamics and suggests that long-range synchronization in the brain results from a bottom-up orchestration process involving the ZPF.